INFORMATION SYSTEM FOR TAX CONSULTANT SERVICE PROVIDERS (C-TAX) BASED ON WEB-BASED WITH MULTI-ATTRIBUTE UTILITY THEORY (MAUT) METHOD - Purnama Suppardi; Benny Daniawan (Jurnal TAM (Technology Acceptance Model), 2022)
Tax is a mandatory contribution to the state owed by an individual or entity that is coercive under the law, with no direct compensation, and used for state purposes. But many people still do not understand taxation, so some people, including taxpayers, need help or consultation from professional, that is Tax Consultants. However, in the digital era, there are still many people who are looking for tax consultants only through recommendations from colleagues or acquaintances. This designed system can help taxpayers in finding tax consultants using the Multi Attribute Utility Theory (MAUT) method, this method can provide tax consultant recommendations based on the selected criteria. Tests carried out on this system uses Technology Acceptance Model (TAM) method based on data obtained from 89 respondents and processed using the Smart-PLS application. The test results found that the five hypotheses were well received because the value of the t-statistics in each assumption was more significant than the t-table value of 1.989 and the p-value smaller than 0.05. In addition, the percentage correlation value of the hypothesis shows that PEOU influences PU by 61%, PU and PEOU influence ATU by 62%, and PU and ATU affect BITU by 47%.